Impact of esketamine intravenous analgesic pump on pain and depression post-cesarean - Xiao-Qiang Zhang; Shuang Li; Xiao-Lin Qin (BMC Surgery)
Abstract Background Postoperative pain and psychological well-being in postpartum women following cesarean section are critical for optimal maternal recovery. Traditional analgesics often have limitations and side effects, prompting the need for alternative solutions. This study evaluates the impact of an esketamine intravenous analgesic pump on postoperative pain and psychological status in postpartum women following cesarean section. Methods A comprehensive retrospective evaluation was conducted at our institution from October 2021 to July 2023, including 168 patients who underwent cesarean delivery. The observation group (n = 82) received esketamine via an intravenous analgesic pump, while the control group (n = 86) received traditional analgesic therapy. Data collected included demographic information, surgical details, postoperative pain (assessed using the Visual Analog Scale, VAS), psychological status (assessed using the Edinburgh Postnatal Depression Scale, EPDS), recovery metrics, and adverse reactions. Results The observation group demonstrated consistently lower VAS scores at all postoperative time points compared to the control group, indicating superior pain control. EPDS scores were significantly lower in the observation group at 3, 5, and 14 days postoperatively, suggesting better psychological outcomes. The incidence of postpartum depression was also lower in the observation group at 3, 5, and 14 days. Recovery metrics such as time to first ambulation, first flatus, and initiation of lactation were significantly improved in the observation group. There were no significant differences in the incidence of adverse reactions between the groups. Conclusions The use of the Esketamine Intravenous Analgesic Pump significantly reduces postoperative pain and the incidence of postpartum depression within the first 14 days. It promotes early recovery and breastfeeding in postpartum women without significant adverse reactions, making it a valuable addition to postoperative care.